The politics of clan reunions ritual, kinship, and cultural transformation among Kankanaeys of northern Luzon - Kibiten, Gaston P. (Ateneo de Manila University Press, 2016)
This work surveys the social, economic, and cultural contexts that have contributed to the recent organization and performance of clan reunions among Kankanaey, and, conversely, the action that these kin reunions perform in these given settings. Moreover, it considers how members of kin groups come together in order to effect integration and solidarity among their ranks, while at the same time examining seriously how social asymmetries and contestations come to play in these new rituals of kinship.